Assessment of left ventricular function by tissue Doppler echocardiography in pediatric chronic kidney disease. (9th August 2015) - Dogan, Cagla Serpil; Akman, Sema; Simsek, Ayse; Ozdem, Sebahat; Comak, Elif; Gokceoglu, Arife Uslu; Kardelen, Fırat; Koyun, Mustafa
Abstract: Background : Cardiovascular (CV) disease remains the most common cause of mortality in chronic kidney disease (CKD). Methods : In this cross-sectional study, 43 pediatric patients with CKD were divided into two groups according to their estimated glomerular filtration rate (eGFR): groups 1 and 2 (eGR; 29–75 and 15–29 mL/min/1.73 m 2, respectively). M – mode, conventional pulsed wave Doppler (cPWD) echocardiography and tissue Doppler imaging (TDI) were performed in all patients and 16 healthy controls. Maximal early ( E wave) and late ( A wave) diastolic flow velocities were assessed by cPWD. Using TDI, the early ( E ′) and late ( A ′) diastolic filling velocities were recorded. Early and late diastoles were evaluated using E ′ values and E / E ′ ratios, respectively. Results : Left ventricular hypertrophy (LVH) was determined in 19/43 (44.2%) patients. The E / E ′ ratio was significantly higher in group 2 than in group 1 and controls. E / E ′ was found to be positively correlated with left ventricular mass (LVM) index, and negatively with hemoglobin (Hb) levels. Low Hb levels were only independent predictor of E / E ′ ( p  = 0.001, β : −0.470, 95% CI: −0.764; −0.196). E ′ ratio was significantly lower in both patient groups compared to the controls. Conclusions : LVH and diastolic dysfunction are already present in early stages of CKD. Treatment of risk factors, such as anemia, is important to improve the clinical outcome.